Flammability of Two Mediterranean Mixed Forests: Study of the Non-additive Effect of Fuel Mixtures in Laboratory - Della Rocca, Gianni; Danti, Roberto; Hernando, Carmen; Guijarro, Mercedes; Madrigal, Javier (Frontiers in Plant Science, 2018)
In the Mediterranean region, wildfires are a major disturbance, determined by ecosystem and forest species characteristics. Both the flammability and resistance to fire of a mixed forest may vary from those of the individual species. Two mixed Mediterranean woodlands, a Cupressus sempervirens and Quercus ilex stand in Italy; and a Juniperus thurifera and Quercus faginea stand in Spain were investigated. Laboratory flammability tests were conducted on live foliage, litter samples and on litter beds from individual and mixed species to evaluate: (i) the flammability traits of the mixtures of live foliage and litter samples; (ii) whether the flammability of the two-species mixtures are non-additive, i.e., differ from expected flammability based on arithmetic sum of the single effects of each components species in monospecific fuel; (iii) the ignition success and initial fire propagation in litter beds. Flammability tests were also conducted on bark samples to estimate the resistance of the tree species to fire. The ignitibility of live foliage was lower and the combustibility was higher in Cupressaceae than in Quercus. Non-additive effects were observed in some flammability components of live foliage and litter, especially in the mixtures of C. sempervirens and Q. ilex. Ignitability and combustibility were higher and lower than expected, respectively, and tended to be driven by Quercus), while the consumability was lowered more than expected by both Cupressaceae. The ignition success in the litter beds was low, especially for the presence of Cupressaceae that increase the bulk density of the mixtures. Cupressaceae, which have a thinner bark, suffered more damage to the cambium after shorter exposure to the heat source than Quercus species. In all the species studied, time to reach lethal temperatures in the cambium was dependent on thickness rather than on flammability of the bark. The study findings revealed that tree species may influence flammability of mixed fuels disproportionately to their load. The studied species showed to exert a contrasted effect on flammability of the mixtures, increasing ignitability and decreasing combustibility and consumability well out of their proportion in the mixture. This may potentially influence fire dynamics in mixed forests.